Peru : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
This Country Financial Accountability Assessment (CFAA) report, looks exclusively at Peru's public sector financial accountability arrangements, and, its primary aim is to assess strengths, and weaknesses, as they relate to the use of Bank funds, particularly under non-investment lending operations. It reviews the legislative framework, relevant to the current reporting environment; the application of appropriate accounting standards, and reporting format, competency of financial staff, and independent review of financial operations and reports, and, the adequacy of financial management, as implied in financial accountability, comprising cash management, planning, control, and supervision of financial operations. Findings and conclusions on the fiduciary framework shows that, as shown by the independent verification of the integrity function assigned under the law to the Supreme Audit Institution (Contraloria General de la Republica - CGR), is undermined by the Executive, through limited funding of its program, while the history of reviews by the CGR indicates a failure to effect, or supervise the external control function in the Ministry of Defense. Furthermore, audit findings reveal that neither the Congress, nor the public is adequately informed on the state of control in the executive branch, suggesting performance auditing should be subject to a cost/benefit analysis, and discussed openly with Congress. Although Peru is considered exemplary in the application of public sector financial management components, its fiduciary framework to support non-investment lending should, however, comprise, in addition to the existing controls, a plan to achieve a strong supreme audit institution to support the extension of the integrated financial management system to the ministries of Defense and the Interior, to ultimately support the uses of funds advanced, and, the external reporting on budget execution should be made at the program level, in addition to restoring the control over Budget to the Congress, limiting the use of Emergency Decrees, and applying transparent guidelines for approved budget funding.